Conceptual math and beyond : precalculus - Tamayo, Joycelyn S.; Villareal, Mary Joy A.; Gatmaitan, Jophel M. (Quezon City : Brilliant Creations Publishing, Inc., 2017)
"This book, Conceptual Math and Beyond (Precalculus), was published by Brilliant Creations Publishing, Inc., to serve as a basic textbook for Precalculus under the Science, Technology, Engineering and Mathematics (STEM) strand. The subject Precalculus deals with concepts and problems involving conic sections, systems of nonlinear equations, series and mathematical induction, circular and trigonometric functions, trigonometric identities, and polar coordinate system."
English text.
Keywords: Precalculus